Hubungan Stunting dengan Keterlambatan Perkembangan Bahasa pada Anak Usia 6-36 Bulan: A Systematic Review - Kirana, Junneka Sarah; Flora, Rostika; Fajar, Nur Alam (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Stunting represents a global public health challenge affecting neurological development in children, particularly language abilities during the critical period of 6-36 months. Chronic malnutrition underlying stunting is suspected to disrupt brain structure and function essential for language acquisition. Objectives: This systematic review aimed to synthesize empirical evidence regarding the association between stunting and language developmental delays in children aged 6-36 months and to explore the underlying neurological mechanisms. Methods: A systematic literature search was conducted across four electronic databases (PubMed, Google Scholar, ScienceDirect, and ERIC) until November 2024 following PRISMA 2020 guidelines. Of 588 records identified, 12 studies met inclusion criteria for analysis. Quality assessment used the Newcastle-Ottawa Scale (NOS). Results: Eleven of twelve studies (91.7%) reported significant associations between stunting and increased risk of language delay (OR: 2.45-4.12). Neurological mechanisms included impaired myelination, synaptogenesis, and reduced brain volume particularly in white matter and corpus callosum affecting language area connectivity. Conclusion: Stunting represents a significant risk factor for language developmental delay through structural and functional brain impairments, emphasizing the importance of nutritional intervention and early stimulation during the critical first 1000 days of life. Keywords: Stunting, Language Development, Speech Delay, Chronic Malnutrition, Neurological Mechanisms.